Women Empowerment Gender Inequality Effect on Economic Development - Jinal Arvindbhai, Jani (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Women Empowerment has become a significant topic of discussion in development and economics. Women's economic empowerment refers to the ability for women to enjoy their right to control and benefit. From the resources assets, income and their own time as well as the ability to manage risk comes empowerment and achieving Gender equality is essential for our society to ensure the sustainable development of a country.
Keywords: women empowerment; economic development; gender equality; sustainable development